A Study On The Key Factors That Lead To Customer Satisfaction In Automobile Industry: A Case Of Perodua - Nur Aneesa Jannah; Nur Aqilah; Nur Atifah; Nur Diyana Hadfini; Sneha Varghese (AIBPM Publisher, 2023)
The Perusahaan Otomobil Kedua Sendirian Berhad (Perodua) is Malaysia's largest car Manufacturer. Perodua was established in 1992 with its headquarters' office located in Rawang, Selangor and currently it has over 200 outlets in Malaysia. Perodua's mission is to provide Malaysians with total mobility through practical and high-value goods and services offered with the utmost care. In the very competitive auto market, manufacturers seek out features for their new models that will help them stand out from their competitors. In 2019, Perodua had recorded the highest market share which is 40% for Malaysian vehicle market. The objective of this research is to analyze the factors that leads customers to feel satisfied with their purchasing from Perodua. A questionnaire would be carried out using a google form to a total of 100 respondents for a data collection. This research finding find out that vehicles' appearances, standing charges and resale value related with customer satisfaction while safety features did not significantly relate with customer satisfaction. The other aim of this research would be to recognize the current degree of consumer loyalty, to distinguish the connection between factors and ultimately to give suggestions/recommendations on the products improvement.